2011
DOI: 10.1007/s11999-011-1805-2
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor CAG Repeat Size is Associated with Stress Fracture Risk: A Pilot Study

Abstract: Level II, prognostic study. See the Guidelines for Authors complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Associations were shown for SNPs and haplotype blocks within the vitamin D receptor (13) and an androgen receptor repeat sequence (14). However, other studies have shown no association for the same SNPs in similar military populations (15).…”
Section: Introductionmentioning
confidence: 90%
“…Associations were shown for SNPs and haplotype blocks within the vitamin D receptor (13) and an androgen receptor repeat sequence (14). However, other studies have shown no association for the same SNPs in similar military populations (15).…”
Section: Introductionmentioning
confidence: 90%
“…This could be explained by military personnel having varying roles that encompass a high level of mobility, leaving DNA extraction to become difficult due to absence during deployment, high workload or travel. The predominant method of blood-based extraction is also time consuming in itself and presents difficulty with either reluctance due to needle use31 or obvious problems in self-gathering blood samples. Although little research has been conducted in comparing DNA extraction methods for genetic studies, research has shown that saliva is becoming an accepted and reliable method of DNA extraction, with applications in self-gathered and field-gathered DNA 18 33…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, larger sized CAG androgen receptor ( AR ) gene repeats (> 16) were more common in Israeli military personnel who had suffered stress fractures (23%) than those who had not suffered this injury (13%) (Yanovich et al 2011). A higher number of CAG repeats within the AR gene are inversely associated with the transcriptional response to testosterone (Zitzmann et al 2001) and deficiency in such hormones could influence bone metabolism and potential bone loss (Mohamad et al 2016; Khosla 2015).…”
Section: Genetic Association With Bmdmentioning
confidence: 99%